Financial Literacy as a Mediating Variable between Financial Behavior and Financial Inclusion: Evidence from Generation Z in Indonesia - Dewi, Monica; Buchdadi, Agung Dharmawan Buchdadi; Mahfirah, Titis Fatarina; Wastuti, Wahyu (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to examine the influence of financial behavior and financial literacy on financial inclusion in Generation Z in Indonesia, which is a productive age group and digital native. Although Gen Z has extensive access to digital financial technology and services, their financial literacy levels are still relatively low, affecting the quality of participation in the formal financial system. This study uses a quantitative approach with a survey method of 120 Gen Z respondents aged 18–24 years, which was analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that financial behavior had a positive and significant influence on financial inclusion (β = 0.410; p < 0.001), which means that the better their financial habits such as saving, budgeting, and managing debt, the higher their participation rate in formal financial services. In addition, financial literacy has also been shown to have a positive and significant effect on financial inclusion (β = 0.350; p < 0.001). Individuals with a strong understanding of financial products, risks, and decision-making tend to be more active and intelligent in using banking, fintech, and other financial instruments. These findings confirm that financial inclusion depends not only on physical access to financial services, but also on the quality of an individual's financial behavior and understanding. Therefore, increasing financial literacy and forming healthy financial behaviors is an important strategy in encouraging sustainable financial inclusion among the younger generation